Molecular methods in identifying the true grouping of erythrocytes in patients with blood system diseases before transplantation of hematopoietic stem cells and their donors - L. L. Golovkina; A. G. Stremoukhova; T. D. Pushkina; B. B. Khasigova; G. V. Atroshchenko; R. S. Kalandarov; L. A. Kuzmina; V. A. Vasilieva; E. N. Parovichnikova (Онкогематология, 2022)
Background. when transplantation of hematopoietic stem cells (HSC) is performing, it is necessary to take into account the incompatibility of the donor and recipient in terms of erythrocyte antigens in order to assess the possibility of immunological complications during HSC transfusion and/or graft engraftment (acute hemolysis, delayed hemolysis, etc.). The results of serological research methods do not always allow identifying the true group affiliation due to posttransfusion chimerism in patients and/or the presence of antigen allelic polymorphism.Aim. To establish the frequency of ABO-incompatible allo-HSC transplantations in the National Research Center for Hematology, to determine by molecular methods the group affiliation of patients with a weakened expression of antigens and/or after multiple blood transfusions before HSC transplantation, to clarify the blood type of HSC donors with a weakened expression of antigens.Materials and methods. The blood of 270 HSC donor-recipient couples was examined. The blood group of the ABO, Rhesus, MNS, Kell systems was determined in a plane agglutination test using the corresponding IgM class Tsoliclones and in gel cards. Genotyping was performed by polymerase chain reaction with primers to identify the genes of the ABO, Rhesus, Kell, and MNS systems.Results. In 2018-2020 270 HSC transplantations were performed at the National Research Center for Hematology. In 141 (52.22 %) couples, incompatibility of the donor and recipient according to the ABO system was revealed: major - 23.33 %, minor - 20 %; bidirectional - 8.89 %. problems in assessing of serological results were observed in 97 (36.3 %) patients: in 78 patients with post-transfusion chimerism and 19 patients with weakened antigen expression; in 15 (5.56 %) HSC donors: in 4 due to the lack of information about the blood group of cryopreserved cells, in 10 due to weakened antigen expression, in 1 to search for informative markers for monitoring HSC engraftment. The results of the study demonstrated that the percentage of agglutinated erythrocytes in post-transfusion chimerism cannot be a reliable criterion for establishing the true phenotype of a patient. In donors and patients with weakened expression of antigens, the presence of ABO*O1, -A1, -A2, -B1, RHD weak type 1, RHD weak type 2, RHD weak type 3, RHCE*Cw genes was confirmed. for the first time in Russia gene RHCE*01.38 was found.Conclusion. The prevalence of ABO-incompatible HSC transplants was noted. problems with serological determination of the blood group in a third of patients before HSC transplantation arose due to the presence of post-transfusion chimerism and weakened expression of antigens. Determining of the genotypes of HSC donors is necessary when the expression of antigens is weakened and cryopreserved cells are received. The percentage of agglutinated erythrocytes in post-transfusion chimerism cannot be a reliable criterion for establishing the true phenotype of a patient. Detection of mixed chimerism in the determination of group factors by serological methods is an indication for genotyping, especially in the context of the predominance of incompatible HSC transplantations.